Mycoepoxydiene Inhibits Lipopolysaccharide-Induced Inflammatory Responses through the of TRAF6 Polyubiquitination - Chen, Qiang (Public Library of Science, 2012)
Mycoepoxydiene (MED) is a polyketide isolated from a marine fungus associated with mangrove forests. MED has been shown to be able to induce cell cycle arrest and cancer cell apoptosis. However, its effects on inflammatory response are unclear. Herein we showed that MED exhibited inhibitory effect on inflammatory response induced by lipopolysaccharide (LPS). MED significantly inhibited LPS-induced expression of pro-inflammatory mediators such as tumor necrosis factor-α (TNF-α), interleukin (IL)-1β, IL-6, and nitric oxide (NO) in macrophages. MED inhibited LPS-induced nuclear translocation of nuclear factor (NF)-κB (NF-κB) p65, IκB degradation, IκB kinase (IKK) phosphorylation, and the activation of extracellular signal-regulated kinase (ERK), c-jun N-terminal kinase (JNK), and p38, suggesting that MED blocks the activation of both NF-κB and mitogen-activated protein kinase (MAPK) pathways. Furthermore, the effects of MED on LPS-induced activation of upstream signaling molecules such as transforming growth factor-β–activated kinase 1 (TAK1), tumor necrosis factor receptor-associated factor 6 (TRAF6) and IL-1 receptor associated kinases1 (IRAK1) were investigated. MED significantly inhibited TAK1 phosphorylation and TRAF6 polyubiquitination, but not IRAK1 phosphorylation and TRAF6 dimerization, indicating that MED inhibits LPS-induced inflammatory responses at least in part through suppression of TRAF6 polyubiquitination. Moreover, MED protected mice from LPS-induced endotoxin shock by reducing serum inflammatory cytokines. These results suggest that MED is a potential lead compound for the development of a novel nonsteroidal anti-inflammatory drug.